Cover, Content, and Editorial Note from Anterior J Vol. 18 No. 1 Desember 2018 - Anterior Jurnal, Chief Editor of (Anterior Jurnal, 2018)
Assalamu’alaikum Wr. Wb. Dear reader, now ANTERIOR JURNAL re-published on Volume 18 Issue 1 December 2018. The success of this publication is the result of good cooperation of all parties who maintain the publishing sustainability twice a year. Alhamdulillah, form this edition ANTERIOR JURNAL has succeeded in gaining a proud achievement by successfully getting an accreditation rating on SINTA 4. This success cannot be separated from the support and prayer of all contributors, both material and non-material. The publication of ANTERIOR JURNAL certainly participates in disseminating the results of research and review of science and technology development conducted by lecturers and researchers especially from UM Palangkaraya and other universities. This edition contains 14 articles consisting of Education, Social and Political, Islamic Studies, Engineering, and Health Science topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition on June 2019. Wassalamu’alaikum Wr. Wb.